1990
DOI: 10.1038/icb.1990.38
|View full text |Cite
|
Sign up to set email alerts
|

Production of a monoclonal allo‐antibody to murine natural cytotoxic cells

Abstract: Summary A mouse IgGi monoclonal antibody (1C4), which recognizes a cell surface molecule on murine natural cytotoxic{NC) cells was produced. By flowcytometry. IC4preferentially reacted with less than 5% of fresh CBA spleen cells and 20-50% of CBA-interleukin-3 (lL-3) cells, an in vitro derived NC-like cell line. In vitro treatment of spleen cells from a number of inbred mouse strains either with 1C4 alone or 1C4 coupled to dynabeads markedly decreased or abolished NC activity of the cells against ^'Cr-labelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Further cellular, functional and biochemical data 88 Natural Cytotoxicity of NC-2 + Cells indicated that NC-2 is not the same receptor as the NC-1.1 receptor identified by moAb 1C4 on cells mediating NC. Mice rendered NC deficient by injection of mAb 1C4 showed reduced tumour surveillance when compared to control mice [20,22]. The in vitro data obtained for mAb D9 suggested that its injection into mice in vivo would also deplete splenic NC.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Further cellular, functional and biochemical data 88 Natural Cytotoxicity of NC-2 + Cells indicated that NC-2 is not the same receptor as the NC-1.1 receptor identified by moAb 1C4 on cells mediating NC. Mice rendered NC deficient by injection of mAb 1C4 showed reduced tumour surveillance when compared to control mice [20,22]. The in vitro data obtained for mAb D9 suggested that its injection into mice in vivo would also deplete splenic NC.…”
Section: Discussionmentioning
confidence: 96%
“…Mice rendered NC deficient by injection of mAb 1C4 showed reduced tumour surveillance when compared to control mice [20, 22]. The in vitro data obtained for mAb D9 suggested that its injection into mice in vivo would also deplete splenic NC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…--Lytic units (LU) were derived from the linear slope of the graph of percent specific lysis vs. E:T ratio (Smart et al, 1990 DAY ANIMALS SACRIFICED FIGURE 3 -Sustained reduction of splenic NK in BALB/c mice treated with repeated injections of MAb 2B6-F2. Groups of 3 BAL,B/c mice were injected i.p.…”
Section: Chromium (Sicr)-release Assaymentioning
confidence: 99%
“…Cells mediating NK or NC in mice can be identified by allo-receptors NK-1.1 (Ryan et al, 1992) and NC-1.1 (Smart et al, 1990;Brien et al, 1994), respectively. Direct evidence for the role of NK-1.1+ and NC-1.1+ cells in tumour immunosurveillance has been provided by the accelerated growth of certain transplantable tumours in mice depleted of these cells (Seaman et al, 1987;Smart et al, 1992).…”
mentioning
confidence: 99%